Do Anti-Bullying Laws Reduce Youth Violence? - Joseph J. Sabia; Brittany Bass (Institute for the Study of Labor (IZA), 2015)
This study is the first to comprehensively examine the effect of state anti-bullying laws (ABLs) on youth violence. Using data from a variety of sources including the Youth Risk Behavior Surveys, Uniform Crime Reports, and newly collected data on school shootings we find that the enforcement of strict, comprehensive school district anti-bullying policies is associated with a 7 to 13 percent reduction in school violence and an 8 to 12 percent reduction in bullying. Our results also show that anti-bullying policy mandates are associated with a reduction in minor teen school shooting deaths and violent crime arrests. A causal interpretation of our results is supported by falsification tests on older young adults for whom ABLs do not bind.
Keywords: I28; 330; bullying; youth violence; anti-bullying laws; school shootings